Liver‐Targeted Small‐Molecule Inhibitors of Proprotein Convertase Subtilisin/Kexin Type 9 Synthesis. Issue 51 (24th November 2017) - McClure, Kim F.; Piotrowski, David W.; Petersen, Donna; Wei, Liuqing; Xiao, Jun; Londregan, Allyn T.; Kamlet, Adam S.; Dechert‐Schmitt, Anne‐Marie; Raymer, Brian; Ruggeri, Roger B.; Canterbury, Daniel; Limberakis, Chris; et al.
Abstract: Targeting of the human ribosome is an unprecedented therapeutic modality with a genome‐wide selectivity challenge. A liver‐targeted drug candidate is described that inhibits ribosomal synthesis of PCSK9, a lipid regulator considered undruggable by small molecules. Key to the concept was the identification of pharmacologically active zwitterions designed to be retained in the liver. Oral delivery of the poorly permeable zwitterions was achieved by prodrugs susceptible to cleavage by carboxylesterase 1. The synthesis of select tetrazole prodrugs was crucial. A cell‐free in vitro translation assay containing human cell lysate and purified target mRNA fused to a reporter was used to identify active zwitterions. In vivo PCSK9 lowering by oral dosing of the candidate prodrug and quantification of the drug fraction delivered to the liver utilizing an oral positron emission tomography 18 F‐isotopologue validated our liver‐targeting approach. Abstract : A liver‐targeting strategy was developed for a small‐molecule drug candidate that inhibits PCSK9 synthesis at the human ribosome. Chemistry enabling the synthesis of N1 tetrazole prodrugs and a companion PET tracer were essential to validating the approach.